Respuesta :

(x + 8)(x - 6)

to factorise consider the factors of - 48 which sum to + 2

These are + 8 and - 6 thus

x² + 2x - 48 = (x + 8)(x - 6)

Answer:

D) x + 8

Step-by-step explanation:

factor. Find factors of x² & -48, in that, when combined, it will give 2x.

x² + 2x - 48

x             -6

x               8

(x - 6)(x + 8)

Check. Follow FOIL method. Combine the first, outside, Inside, & Last terms:

(x * x) = x²

(x * 8) = 8x

(x * -6) = -6x

(-6 * 8) = -48

x² + 8x - 6x - 48

x² + 2x - 48 (√)

Your answer choices:

(x - 6) & (x + 8)

x + 8 shows up as a choice, so D) x + 8 is your answer.

~

ACCESS MORE